Crisis financieras y crisis bancarias: Revisión de literatura y aproximación a elementos de control para el futuro - Irene Clara Pisón Fernández; Félix Puime Guillén; Miguel Ángel Crespo Cibran (Atlantic Review of Economics, 2015)
– The existence of crisis processes recommends, following the Keynesian theory, the need for a degree of public intervention as a necessary factor for the management of imbalances caused in markets that require regulation, together with support and recovery policies. According to monetarist theory , this cyclical occurrence of crisis in the globalized economy is caused by an irrational use of factors of production, which means that, in periods of stagnation or recession , there are imbalances that the system itself is not capable of corrected through usual actions . Control models of credit risk in the banking sector should incorporate elements that take into account these factors.
Keywords: G01; 330